PROSPEK KULIT SEMANGKA SEBAGAI BAHAN PENGELOLAHAN MANISAN KERING UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT DESA BEDAH LAWAK, KABUPATEN JOMBANG - ,, Zulfikar; Qomariyah, Siti Nur; Maulinddia, Eli Zahrotul; Annafis, Mochammad Iqbal; ., Yunaidah (ABDI WINA JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Watermelon pulp is a waste material from the part of the fruit that is consumed by the community but is neglected. The use of watermelon pulp in addition to reducing household waste, also still has sufficient nutritional content so that it has the potential to be processed as an ingredient for making dried sweets. This community service activity aims to train PKK women in Bedah Lawak village to be able to use watermelon skin as an ingredient for making dried sweets so that they can improve the family economy. The training method was through a workshop on making dried sweets which was attended by 18 PKK women. The results of this service activity showed that PKK mothers were able to understand the making of dried sweets which was indicated by an increase in the level of understanding by 15,9%. The production of dried sweets made by PKK women in Bedah Lawak village is able to contribute as a superior product which is facilitated by the village government.